Integrity links ethics and efficiency in nursing leadership: Nurse leaders’ views - Salmela, Susanne (Nursing ethics, 2026)
Background Today?s healthcare organizations are organized to provide effective, efficient care that yields good patient outcomes. Healthcare leaders must be capable of engaging in both leadership relevant to human relationships and the management of processes.Aim The aim of this study was to explore nurse leaders? perceptions of integrity in enhancing nursing leadership that is both effective and ethical.Research design, participants, and research context A qualitative exploratory design with qualitative content analysis as method was undertaken, including multistage focus group interviews with 9 nurse leaders in a hospital setting.Ethical considerations The study was conducted in accordance with the guidelines of the Finnish National Board on Research Integrity and the Declaration of Helsinki.Findings One main category and three subcategories were seen. The main category was ?Integrity links ethics and efficiency?.Discussion Integrity was seen as a part of ethical leadership. Integrity was also seen as nurse leaders? values shaped by personality and work experience. To lead with efficiency was seen as part of knowledge-based leadership.Conclusions Integrity allows nurse leaders to interweave ethical values and efficiency, thereby realizing nursing leadership that is ethical and effective and leading to care that is of good quality.